Difamilast, a selective phosphodiesterase 4 inhibitor, ointment in paediatric patients with atopic dermatitis: a phase III randomized double‐blind, vehicle‐controlled trial. (1st November 2021) - Saeki, H.; Baba, N.; Ito, K.; Yokota, D.; Tsubouchi, H.
Summary: Background: In atopic dermatitis (AD), phosphodiesterase 4 (PDE4) inhibition reduces proinflammatory mediators and cytokines. Difamilast is a new selective PDE4 inhibitor. Objectives: To demonstrate the superiority of topical difamilast to vehicle in Japanese paediatric patients with AD. Methods: This was a phase III randomized, double‐blind, vehicle‐controlled trial. Patients aged 2–14 years with an Investigator Global Assessment (IGA) score of 2 or 3 received difamilast 0·3% ( n  = 83), difamilast 1% ( n  = 85) or vehicle ( n  = 83) ointment twice daily for 4 weeks. Results: The primary endpoint was the percentage of patients with an IGA score of 0 or 1 with improvement by at least two grades at week 4. The success rates in IGA score at week 4 were 44·6%, 47·1% and 18·1% in the difamilast 0·3%, difamilast 1% and vehicle groups, respectively. Both difamilast groups demonstrated significantly higher success rates in IGA score compared with vehicle at week 4 [difamilast 0·3% ( P < 0·001 ); difamilast 1% ( P < 0·001 )]. Regarding secondary endpoints, improvements in Eczema Area and Severity Index (EASI; improvement of ≥ 50%, ≥ 75% and ≥ 90% in overall score) at week 4 were significantly higher in patients in the difamilast 0·3% and 1% groups than those in the vehicle group. EASI score in the difamilast 0·3% and 1% groups was significantly reduced compared with that of patients in the vehicle group at week 1. The significant difference between both the difamilast groups and the vehicle groups was maintained from week 1 through to week 4. Most treatment‐emergent adverse events were mild or moderate, and no serious events or deaths were reported. Conclusions: Difamilast 0·3% and 1% ointments are superior to vehicle and well tolerated in Japanese paediatric patients with AD. Abstract : What is already known about this topic? In atopic dermatitis (AD), increased phosphodiesterase 4 (PDE4) activity leads to a proinflammatory milieu involved in acute and chronic inflammation. Topical inhibitors of PDE4 are available and are an alternative to topical corticosteroids or calcineurin inhibitors for AD. Concern about the adverse effects of topical corticosteroids or calcineurin inhibitors may limit their use in the treatment of AD. What does this study add? This trial demonstrates the efficacy of the selective topical PDE4 inhibitor difamilast for mild‐to‐moderate AD in Japanese paediatric patients. Difamilast is well tolerated with an adverse event profile similar to vehicle. Linked Comment:  D.M.W. Balak and E. Hajdarbegovic. Br J Dermatol 2022; 186:5–6 . Plain language summary available online